Effect of heme arginate administration on blood pressure in spontaneously hypertensive rats. - Levere, R D (1990)
Cytochrome P450 content and activities are increased in the kidneys of spontaneously hypertensive rats (SHR) as compared with those of normotensive, Wistar-Kyoto (WKY), control rats during the period of rapid elevation of blood pressure. We studied the effect of heme arginate, a potent inducer of heme oxygenase (EC 1.14.99.3), on microsomal cytochrome P450 levels and activities and blood pressure in SHR at 7 wk of age. Administration of heme arginate (15 mg/kg body weight for 4 d) resulted in a marked decrease in blood pressure from 156.3 +/- 4.7 to 129.8 +/- 4.5 mm Hg (P less than 0.001), whereas blood pressure in SHR receiving the vehicle control was not affected. The blood pressure of age-matched WKY was not affected by heme arginate. Heme oxygenase activity increased in both hepatic and renal microsomes of SHR and WKY by two- to four-fold after treatment with heme arginate. Maximal increase of heme oxygenase mRNA occurred 5-7 h after the last injection of heme arginate and returned to control levels after 24 h. The increase in heme oxygenase activity was associated with a parallel decrease in cytochrome P450 content and in the activity of cytochrome P450 omega/omega-1 arachidonate hydroxylases in kidneys of SHR. It is postulated that heme arginate treatment resulted in induction of heme oxygenase which consequently led to a diminution of cytochrome P450, especially the arachidonate omega/omega-1 hydroxylases leading to a marked decrease in 19-hydroxyeicosatetraenoic acid (HETE) and 20-HETE. The effect of heme arginate on blood pressure may be mediated via these biochemical events inasmuch as both 19-HETE and 20-HETE produced by the kidney may promote hypertension by causing vasoconstriction and sodium retention.